SPONTANEOUS PERFORATION OF BILE DUCT, CLINICAL PRESENTATION, LABORATORY WORK UP, TREATMENT AND OUTCOME - Malik, Hassan Suleman; Cheema, Huma Arshad; Fayyaz, Zafar; Hashmi, Muhammad Almas; Parkash, Arit; Waheed, Nadia; Mushtaq, Iqra; Anjum, Muhammad Nadeem (Journal of Ayub Medical College Abbottabad, 2016)
Background: Spontaneous perforation of bile duct (SPBD) is a rare and often misdiagnosed entity. Though rare, it is the second most common surgical cause of jaundice in infants, after biliary atresia. This study was planned to determine the clinical presentation, study different diagnostic modalities, treatment and outcome of patients with spontaneous perforation of bile duct. Methods: This descriptive case series, comprising 22 patients with spontaneous perforation of bile duct over a period of 24 months. Clinical presentation, biochemical abnormalities, imaging details, treatment options and outcome were studied. Results: Total 22 patients (12 Males and 10 Females) between ages of 1.5-36 months were studied. Associated anatomical defects included choledochal cyst in 7 (31.8%) while acquired biliary atresia in 1 (4.5%). Elevated liver enzymes (ALT and AST) were present in 16 patients (72.7%) and 5 (22.7%) had bilirubin above 3 mg/dl. Coagulopathy was seen in 8 (36.6%) patients. Abdominal USG showed presence of ascites in all 22 (100%), hydrocele in 2 (9.0%), inguinal hernia in 1 (4.5%), choledochal cyst in 7 (31.8%) and atretic gall bladder suggestive of acquired biliary atresia in one (4.5%) patient. HIDA scan was diagnostic in all 17 (77.27%) in which it was performed. MRCP was done in 3 (13.6%) patients. Mortality frequency was 3/22 (13.6%); one died of post-surgical sepsis second one was cirrhotic at time of presentation and didn't make It. Two were lost to follow up one which died at home while we lost contact with fourth patient. Conclusion: Spontaneous perforation of bile duct can present and should be suspected as an important cause of neonatal biliary ascites or peritonitis. Most patients can be managed with intravenous antibiotics, percutaneous drainage and t-tube insertion while patients with choledochal cysts required cholecystectomy with roux en y choledochjejunostomy. Timely recognition and intervention is associated with favourable outcome. Keywords: Spontaneous perforation of bile duct, clinical features, choledochal cyst, treatment, paediatric